Depression in High-Risk Type 2 Diabetes Adults. Issue 3 (July 2020) - Mathur, Deepali; Anand, Akshay; Srivastava, Vinod; Patil, Suchitra S.; Singh, Amit; Rajesh, SK; Nagendra, HR; Nagarathna, Raghuram
Background: Patients suffering from diabetes mellitus are two to three times more vulnerable to develop depressive symptomatology. Purpose: To report the association between depression and high-risk diabetes in India. Methods: A total of 1, 606 adults were recruited for the study. A patient health questionnaire was used to determine the depression on the basis of score. A statistical analysis was done using analysis of covariance (ANCOVA) and binary logistic regression to determine the association between diabetes categories and four degrees of depression. Results: Out of 1, 606 participants, 52.6% were males and 47.4% were females, 56.4% belonged to the urban area and 43.6% to the rural area. However, 19.5% (314) had diabetes; 29.1% of diabetes individuals had minimal depression, 38.7% had mild, 17.2% moderate, 12.0% moderately severe, and 3.1% had severe depression. In the self-reported diabetic participant group ( N = 142), there was a significantly higher degree of severe depression (3.3%) in the uncontrolled group (HbA1c >7%) as compared to the well-controlled diabetes group (HbA1c <7%). ANCOVA in gender differences in the uncontrolled diabetes group showed that male gender had significantly ( P = –.02) higher mean scores of depression. Conclusion: This study found that there is a positive association between depression and uncontrolled diabetes in male gender.